EFEKTIVITAS MANAJEMEN PEMBELAJARAN PENDIDIKAN CALON GURU PENJAS ORKES DI FAKULTAS PENDIDIKAN OLAHRAGA DAN KESEHATAN FPOK UNIVERSITAS PENDIDIKAN INDONESIA UPI BANDUNG - Supriadi, Andri (2012)
Quality education is a key condition for realizing the life of a developed nation, modern and prosperous. Teachers have an important role in achieving quality education, including physical education teachers. Some conditions on the ground shows the persistence of the physical education teachers who have competency has not been as expected. Creating a physical education teacher is the primary role of the college, one of which is the Faculty of Sport and Health UPI Bandung. One indicator of success is the index value learning achievements of students. In FPOK UPI still low student achievement and graduation index is not timely.Many factors determine the quality of physical education teacher candidates are generated. One is the application of management education at the university. The purpose of this study was to analyze the effectiveness of management education in FPOK UPI sports. The study was conducted with a qualitative method of grounded theory. As research subjects (the informant) is Dean, Chairman of the Department and students FPOK UPI Bandung. Data were collected by interviews using an interview guide. The results of this study is planning educational program begins with the preparation of the curriculum, then translated in the syllabus, SAP and Handouts. Each course is equipped with teaching materials prepared by the team teaching of the course. But in planning educational programs not to mention the attention to the ability of every student that is still yet to see the global nature of the initial ability of each individual is taught. The process of education takes the form of two models of education in the classroom (indoor) for educational theory and education outside the classroom (outdoor) for educational practice. Educational approach to teaching the practice carried out by way of the game for understandly educational approach to understanding patterns play the sport. It is not yet visible on the educational process related to the techniques taught by the student as a candidate for re-associated with the profession as a teacher of physical education teachers. Development of educational materials is done by researching and using the literature up to date. The studies conducted by faculty and research results are used to develop teaching materials. Development of teaching materials do a good material for educational theory and practice of learning. In general competence development has been done well, especially for pedagogical competence, professional and personality. However, competence development is still done in the usual way, have not seen any innovation in the development of student competence. Especially for the development of social competence was conducted in a group of students and have not seen the development of social competence in social life. Overall learning management education high school gym teacher candidates have not been effective in FPOK UPI. Necessary to identify the beginning of student ability, the innovation in the development of methods, materials and the development of student competence and the necessary development of teaching materials in a comprehensive and continuous.